Análise do desempenho elétrico de um gerador fotovoltaico com o auxílio da tecnologia PVT - Guerra, Maria Izabel da Silva (2016)
Photovoltaic technology for electric power generation still presents a high investment cost and, due to its relatively low efficiency, the market is sometimes restricted and unattractive. The solar irradiance and the cell surface temperature are the two main factors that influence in the electricity production of the photovoltaic cell. While increased solar irradiance raises the production of electrical power, the increase in temperature reduces the generation of energy. So, a way to make this technology more interesting is to perform the cooling of the photovoltaic cell by means of photovoltaic and thermal hybrid technology, which allows to simultaneously convert the available solar energy into both electricity and heat. Thinking about that, the present research aimed to test and analyze the electric performance of a commercial photovoltaic generator with some adaptations that allowed the coupling of a cooling system with water, and to compare it with the performance of a commercial photovoltaic generator without a cooling system. In addition, to support the analysis and discussion of the results and to estimate the behavior of a photovoltaic generator with one or more solar cells, two thermal models were developed to analyze the presence of the cooling system. The thermal models were simulated with the aid of Matlab® software. From the results obtained in the simulation, it was verified that: for irradiance levels of 1000W/m² and the ambient temperature of 30°C, without the cooling system, the temperature of a crystalline silicon photovoltaic cell with a nominal power of 4,58Wp (the Standard Test Conditions 1000W/m² and 25°C) would increase to approximately 71°C, which corresponds to an electric power of 3,654W and an electric efficiency of 15%. However, with the cooling system coupled to the solar cell with water at 30°C, as the cooling fluid, the cell surface temperature would reduce to approximately 32°C, allowing a production of 4,414W of power and an electric efficiency over 18%. When testing the made prototype, a temperature of approximately 65°C for the system composed only of the PV cell was measured using a sensor, which shows an error of 8,7% between the estimated temperature in the simulation and that measure in the prototype test. From the measured surface temperature, a power of 3,762 W produced by the solar cell and an electrical efficiency of 15,46% were estimated. In the tests performed on the prototype with a cooling system, the temperature verified was approximately 32°C, that is, a 20% error when compared to the simulation, but that provides a power of 4,257W and an electric efficiency of 17,5%. At the end of this study, it was possible to observe that the PVT hybrid technology is promising, since the photovoltaic cell, thanks to its thermal characteristics, can easily be cooled by water along copper tubes coupled to its posterior face.